EFL Young Learners’ Strategies in Dealing with Requests: Language and Pragmatic Transfer Analysis - Torieq Abdul Muis; Lies Amin Lestari; Ahmad Munir (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2022)
Abstract Maintaining communications among teacher-students or student-student is crucial in EFL classroom settings. EFL learners of beginner levels often find themselves in challenging situations in dealing with new language concepts they learn. As a result, they frequently come up with strategies that teachers occasionally fail to comprehend. This paper aims at investigating the speech act of requests used by young EFL learners in communicating their thoughts. This qualitative study focuses on how EFL learners employ requesting strategies in L2 utterances and the roles of pragmatic and language transfer in the process. Data were collected from 20 EFL learners of lower language proficiency through classroom oral activities. This study sees L1 transfer as a phenomenon that contributes to a successful classroom communication. The findings demonstrate that language and pragmatic transfer play a pivotal role in the learners’ requesting strategies. To deal with pragmatic transfers, young learners tend to use indirect speech acts by delivering repeated requests as the strategy that potentially encompass hidden intentions or messages. On the other hand, linguistic transfers initiated the learners to utilize raising intonation strategy in affirmative statements for making requests. This study also suggests that teaching English as L2 to young learners should also take account of the pragmatic knowledge besides linguistic competence. Keywords: Language transfer; Pragmatic transfer; Speech acts; EFL young learners Abstrak Menjalin komunikasi antar guru-siswa atau siswa-siswa penting adanya dalam konteks kelas pembelajaran EFL (Inggris sebagai Bahasa Asing). Pelajar EFL tingkat pemula sering kali berada dalam situasi yang menantang kemampuan berbahasa ketika dihadapkan dengan konsep bahasa baru yang mereka pelajari. Akibatnya, mereka tak jarang melakukan strategi yang terkadang gagal dipahami oleh guru. Makalah ini bertujuan untuk menyelidiki tindak tutur permintaan yang digunakan oleh pelajar EFL muda dalam mengkomunikasikan pemikiran mereka. Studi kualitatif ini berfokus pada bagaimana pelajar EFL menggunakan strategi meminta dalam ucapan L2 (Inggris) dan peran transfer pragmatis dan transfer bahasa dalam prosesnya. Data dikumpulkan dari 20 pelajar EFL dengan kemampuan bahasa rata-rata pemula melalui kegiatan lisan di kelas. Studi ini melihat proses transfer bahasa L1 (Indonesia) sebagai fenomena yang berkontribusi pada keberhasilan komunikasi kelas. Temuan menunjukkan bahwa transfer pragmatis dan bahasa memainkan peran penting dalam strategi mengungkapkan permohonan. Untuk menghadapi transfer pragmatis, pelajar muda cenderung menggunakan tindak tutur tidak langsung dengan strategi penyampaian permintaan berulang yang berpotensi memuat maksud atau pesan tersembunyi. Sedangkan transfer linguistik memprakarsai pelajar muda untuk menggunakan strategi intonasi meninggi dalam pernyataan afirmatif untuk membuat permintaan. Studi ini juga menyarankan bahwa pengajaran bahasa Inggris sebagai bahasa asing atau kedua untuk pelajar muda juga harus memperhitungkan pengetahuan pragmatis selain kompetensi linguistiknya. Kata kunci: transfer bahasa, transfer pragmatis, tindak tutur; pelajar muda EFL